PENINGKATAN KETAGGAPAN WARGA PESISIR TERHADAP BENCANA BANJIR ROB : WARGA TANGGUH BENCANA - Nurainun Apriani Idris, Baiq; Hadi, Irwan; Ariyanti, Maelina; Supriyadi, Supriyadi; Hapipah, Hapipah (Stikes Yarsi Mataram, 2024)
Introduction: Unexpectedly high sea water can cause flooding which can damage, threaten lives and endanger the community, especially residents who live close to the shoreline or coastline. Objective: increase the response capacity of coastal residents to tidal flood disasters. Method: conducting outreach and simulating tidal flood disasters. Results: The average posttest score reached 17.5 out of a maximum score of 20, indicating the success of counseling in increasing respondents' knowledge and preparedness. Conclusion: Increasing community understanding, as reflected in a high average posttest score, can make a significant contribution to increasing community preparedness and adaptation to the risk of tidal floods. Furthermore, efforts are needed to maintain this positive momentum through sustainable programs, collaboration with related parties, and strengthening community participation in mitigation efforts.